Mendorong Kemajuan UMKM Desa Toapaya Melalui Pendampingan Pembuatan Nomor Induk Berusaha (NIB) - Disya Putri Kamalia; Viona Pramesty Eka Putri; Afriyona Putri; Rani Nabila; Qoriah Rahmadiah Ismail; Adithya Baby Pratama Pudi; Jingga Indraini; Dio Gelvanda; Febriyansah Febriyansah (Pusat Riset dan Inovasi Nasional, 2025)
The Community Service Program (KKN) of Raja Ali Haji Maritime University in Toapaya Village has a work program that aims to encourage the advancement of Micro, Small, and Medium Enterprises (MSMEs) by facilitating the creation of Business Identification Numbers (NIB). This study uses a descriptive qualitative approach to understand the process, challenges, and impact of business legality on MSME actors. The results of the activity show that NIB ownership provides significant benefits, including increasing business legality and credibility, expanding access to capital, and opening opportunities to participate in various government programs. The assistance process was carried out through socialization, data collection, technical assistance, and NIB distribution. Despite facing obstacles such as limited digital literacy, internet access, and resistance to change, the collaboration between KKN students, the village government, and related agencies succeeded in helping MSME actors obtain NIBs effectively. With business legality, MSMEs in Toapaya Village were able to increase their competitiveness, expand their marketing networks, and strengthen their role in village economic development. This program proves that MSME empowerment based on business legality can be an important foundation for village independence and sustainable economic growth.